Improvement of Pulmonary Hypertension In A Transplant Patient - Fatima, Faiqa; Rizvi, Nabiha (Pakistan Journal of Kidney Diseases, 2021)
Pulmonary hypertension is not an uncommon finding in patients on hemodialysis. This is usually cardiac in origin including left ventricular failure or diastolic dysfunction. Arteriovenous fistula causing high flow in the venous return may lead to pulmonary hypertension and right sided failure. We here report a patient with pulmonary hypertension post kidney transplantation that did not respond to management over a period of 3 years and ultimately improved significantly after closure of arteriovenous fistula created for hemodialysis pre-transplant.